Application of 5‐aminolevulinic acid‐photodynamic therapy in common skin diseases. Issue 1 (15th April 2020) - Shi, Lei; Liu, Pei; Liu, Jia; Yang, Yuling; Chen, Qi; Zhang, Yunfeng; Zhang, Haiyan; Wang, Xiuli
Abstract: 5‐Aminolevulinic acid‐photodynamic therapy (ALA‐PDT) is a relatively novel therapeutic technique that is used widely in dermatology. ALA can penetrate the stratum corneum into the skin and convert to the protoporphyrin IX (PpIX) to exert the photodynamic response. Due to its advantages of allowing repetitive application to multiple lesions, non‐trauma and excellent cosmetic results, ALA‐PDT is widely used for the treatment of actinic keratosis, moderate and severe acne, condyloma acuminate and other skin diseases showing a strong or promising effectiveness. However, pain is the main adverse reaction of ALA‐PDT. Daylight PDT (D‐PDT) and an optimized PDT may relieve the pain through the change of light source and therapeutic parameters. Both will be the tendency of the clinical application of ALA‐PDT. Abstract : 5‐Aminolevulinic acid‐photodynamic therapy (ALA‐PDT) is a relatively novel therapeutic technique. Due to its advantages of allowing repetitive application to multiple lesions, non‐trauma and excellent cosmetic results, ALA‐PDT is widely used for the treatment of actinic keratosis, moderate and severe acne, condyloma acuminate and other skin diseases showing a strong or promising effectiveness. However, pain is the main adverse reaction of ALA‐PDT. Daylight PDT and an optimized PDT may relieve the pain through the change of light source and therapeutic parameters.